PEMIKIRAN POLITIK RASYID RIDHA DALAM FIQH MUNAKAHAT - Hadi, Khoirul (State Institute of Islamic Studies (IAIN) Palu, 2013)
Abstract. This article discusses the political thought of Rida Muhammad Rashid Rida in his work in the field of Fiqh Muhakahat. There are several themes that will be discussion, among them: Nationalism in Rida view, the state system, Islamic and Western modernity, and political thought of Rida in fiqh munakahat. In the fiqh munÄkahÄt, Ridha still confined by the influence of classical scholars, such as not being allowed to marry a Muslim woman with a non-Muslim (Ahl al-KitÄb). Though the social context between the communities in the past different with the social context in the Ridha lifetime. This is what apparently needs to be studied carefully.Kata kunci: Â Â Â Â pemikiran politik, fiqh munÄkahÄt, nasionalisme, tata negara